2010
DOI: 10.1086/656243
|View full text |Cite
|
Sign up to set email alerts
|

Successful Eradication of a Monoclonal Strain ofKlebsiella pneumoniaeduring aK. pneumoniaeCarbapenemase-ProducingK. pneumoniaeOutbreak in a Surgical Intensive Care Unit in Miami, Florida

Abstract: We describe the investigation and control of a Klebsiella pneumoniae carbapenemase-producing K. pneumoniae outbreak in a 20-bed surgical intensive care unit during the period from January 1, 2009 through January 1, 2010. Nine patients were either colonized or infected with a monoclonal strain of K. pneumoniae. The implementation of a bundle of interventions on July 2009 successfully controlled the further horizontal spread of this organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 12 publications
(16 reference statements)
0
43
0
2
Order By: Relevance
“…However, early data have suggested that combination therapy may be beneficial in bacteremia caused by KPC-producing K. pneumoniae (21). Rapid detection would therefore allow early examination of antimicrobial options and initiation of recommended infection control precautions to avert institutional outbreaks (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…However, early data have suggested that combination therapy may be beneficial in bacteremia caused by KPC-producing K. pneumoniae (21). Rapid detection would therefore allow early examination of antimicrobial options and initiation of recommended infection control precautions to avert institutional outbreaks (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Isolation or cohorting of CPE carriers seems to be the main prevention measure (43,83,106,110,122,127,176,177,234). Assignment of dedicated health care workers and use of separate equipment for carriers are additional interventions that have been employed successfully in several outbreaks (19,43,122,176,177,234).…”
Section: Interventionmentioning
confidence: 99%
“…In another study, Enfield et al were successful in decreasing the CPE incidence in a surgical ICU from 7.77 cases per 1,000 patient-days to 1.22 cases per 1,000 patient-days by using enhanced infection control measures and increased surveillance by implementing a PCR-based assay (82). Two outbreaks of KPCproducing organisms were successfully controlled by using a "bundle approach," of which screening for CPE carriage is an integral part (83,84). Schwaber et al reported on a country-wide mandatory program involving physical isolation and dedicated nursing staff in Israel that was able to significantly decrease the incidence of KPC-producing isolates (85).…”
Section: Intestinal Carriage Of Cposmentioning
confidence: 99%